Development of a Local-Culture-Based Arabic Conversation Book to Support Junior High School Students’ Mahārah Kalām - Bambang Irawan; Renti Yasmar; Arini Salsabila; Fathul Ulum; Muhamad Turki (Institut Agama Islam Negeri Curup, 2026)
Mahārah Kalām learning at the junior secondary school level still faces fundamental challenges, particularly students’ low confidence, limited fluency, and difficulty in expressing simple ideas orally in Arabic. These problems are closely related to the dominance of reading, translation, and vocabulary memorisation in classroom practices, as well as the limited availability of Arabic conversation books that provide communicative, contextual, and locally relevant speaking activities. This study aims to develop a local-culture-based Arabic conversation book to support meaningful Mahārah Kalām learning for junior high school students. The study employed a research and development approach using the ADDIE model, combined with a convergent parallel mixed methods design. The data were collected through needs analysis, classroom observation, teacher interviews, student responses, expert validation, and a limited trial involving 13 students, one Arabic teacher, one material expert, and one instructional design expert. The needs analysis revealed the necessity of contextual dialogues, familiar local themes, guided speaking practice, role-play activities, and culturally relevant visual materials. The developed book integrates Situbondo local culture into vocabulary, dialogue models, speaking tasks, and role-play scenarios. Expert validation indicated that the product was feasible in terms of content and design, while the limited trial showed positive student and teacher responses regarding acceptability, clarity, and practicality. This study suggest that a locally culture-based Arabic conversation book can serve as an alternative communicative teaching material to improve Mahārah Kalām learning in Indonesian junior secondary schools.